2004
DOI: 10.1111/j.1523-1755.2004.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective lymphocyte inhibition by FTY720 slows the progressive course of chronic anti-thy 1 glomerulosclerosis

Abstract: Lymphocyte depletion by FTY720 limits the progression of anti-thy 1-induced glomerulosclerosis toward chronic tubulointerstitial fibrosis and renal insufficiency. The data suggest that lymphocytes actively participate in the progression of chronic experimental kidney disease, and that FTY720 may be a novel approach to slow the progressive course of human chronic renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 35 publications
3
75
1
Order By: Relevance
“…Glomeruli from individual rats were isolated by a graded sieving technique (160-, 125-, and 71-m mesh metal sieves), as described previously (17,22,27). For cultures of renal cortical tissue, a piece of cortical tissue was weighed and minced extensively with a razor blade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomeruli from individual rats were isolated by a graded sieving technique (160-, 125-, and 71-m mesh metal sieves), as described previously (17,22,27). For cultures of renal cortical tissue, a piece of cortical tissue was weighed and minced extensively with a razor blade.…”
Section: Methodsmentioning
confidence: 99%
“…After 48-h incubation at 37°C/5% CO 2, supernatants were harvested and stored at Ϫ70°C until analysis of TGF-␤1 or TIMP-1 content. TGF-␤1 and TIMP-1 content of the culture supernatant was measured after acid activation, using commercially available ELISA kits (TGF-␤1 and TIMP-1 Duoset, R&D Systems, Wiesbaden, Germany) according to the manufacturer's instructions (17,22,27). Three samples from each rat were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Progression in chronic anti-thy1 GS is not primarily immune mediated. It is rather an experimental paradigm for a "one-hit, self-progressing kidney disease," as it is seen in patients with deteriorating renal function and a transient glomerulonephritic episode in the past (18). Control animals with and without uninephrectomy were injected with equal volumes of PBS only.…”
Section: Induction Of Anti-thy1-induced Chronic-progressive Gsmentioning
confidence: 99%
“…In a model of antibody-induced, chronic-progressive renal fibrosis, i.e., anti-thy1-induced chronic glomerulosclerosis, we have previously reported that selective inhibition of lymphocyte migration into the diseased kidney by FTY720 significantly limited the progressive course of the disease toward glomerulosclerosis and tubulointerstitial fibrosis (21). FTY720 {fingolimod; 2-amino-2-[2-(4-octylphenyl)ethyl]-1,3-propanediol hydrochloride} is a novel and potent lymphocyte-specific immunomodulator and has currently been tested in phase III studies for the treatment of multiple sclerosis (3,10).…”
mentioning
confidence: 99%